FROZEN SHOULDER: OUTCOME OF INTRA-ARTICULAR STEROID INJECTION IN IDIOPATHIC ADHESIVE CAPSULITIS IN TERMS OF PAIN RELIEF AND RANGE OF MOTION - Khan, Muhammad Waqar; Ibrahim, Muhammad; Ullah, Sana; Khan, Imran; Khan, Zeeshan; Khan, Muhammad Arif (Journal of Postgraduate Medical Institute, 2021)
Objective: To find out the outcomes of intra articular steroid injection in idiopathic adhesive capsulitis, in terms of pain control and functional activity. Methodology: This Quasi experimental study was conducted in the Department of Orthopedic and Spine, Hayatabad Medical Complex, from February 2019 to February 2020. All patients aged above 18 years of age, both genders, having a diagnosis of idiopathic adhesive capsulitis were included in this study. A total of 200 patients were included in the study. Sample size was calculated by Open-Epi. Their pre injection Shoulder Pain and Disability Index (SPADI) and Visual Analogue Score (VAS) were recorded. All patients received intra-articular corticosteroid injection. SPADI and VAS were recorded after 4 and 12 weeks. The baseline scores and those recorded at follow up after injection were compared. Data was analyzed using SPSS version 23. Results: Out of 200, 86 (43%) were female and 114 (57%) were male. The average age of our patients was 50.85 (±7.36). Their average pre injection SPADI was 79 (±6.4) while the average VAS was 6.5 (±0.9). Mean evaluation scores at 4th week of intra-articular corticosteroid injections were improved to SPADI 27.32 (±3.14) and VAS was 2.55 (±1.1) with a statistically significant p-value of 0.0001. At 12th week SPADI disability score was still consistent at 27 (±3) but their VAS score worsened to 6.1 (±0.86). Conclusion: Patients suffering from idiopathic adhesive capsulitis can benefit from intra-articular corticosteroid injection alone. The range of motion and functional ability in their diseased shoulder can get better till 12 weeks. Their pain, on other hand, will get better initially but later on it’ll re-appear and would warrant re-evaluation and change in management plan.